STRATEGI KOMUNIKASI POLITIK PARTAI NASDEM DALAM MENINGKATKAN ELEKTABILITAS ANIES BASWEDAN MENJELANG PEMILIHAN PRESIDEN 2024 - Amelia Rinandya (2023)
The background of conducting this research lies in the declaration of the National Democratic Party to endorse Anies Baswedan as a presidential candidate, regardless of the fact that Anies Baswedan is not a party member. Moreover, it is noteworthy that the NasDem Party's position remains within the coalition house. The NasDem Party's decision to support Anies Baswedan is a significant departure from their previous stance. In the previous general elections of both 2014 and 2019, the party chose to remain in the coalition of President Joko Widodo. Throughout two general elections from 2014 to 2019, the NasDem Party has experienced the most significant increase compared to other parties. The NasDem Party is also the youngest party to enter the top five in the general elections held in the previous year of 2019. The objective of this research is to investigate the political communication strategies employed by the NasDem Party to enhance the electability of Anies Baswedan in the lead-up to the Presidential Election in 2024. It should be noted that the research adopts a qualitative method, utilizing interview techniques as the primary data source, and utilizing articles, books, journals, and other sources as secondary data sources. The research findings indicate that the NasDem Party employs a political communication strategy consisting of political persuasion techniques, including political propaganda, political advertising, and political rhetoric.